1998
DOI: 10.1007/s11626-996-0011-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute cytotoxicity testing with cultured human lung and dermal cells

Abstract: An extensive in vitro study with cultured cells was conducted to test the basal cytotoxicity theory. This theory suggests that most chemical injury, at least in vitro, is a manifestation of one or more insults to the basic cellular structures and functions common to mammalian cells. This accounts for the similarity of results in multilaboratory studies. Human fetal lung fibroblasts (HFL1), and human skin fibroblasts (WS1, Detroit551) were studied in culture to evaluate their potential to screen for cytotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Cells were harvested and radioactivity was measured as previously described (Barile and Cardona 1998; Barnes et al ., 1990). …”
Section: Methodsmentioning
confidence: 99%
“…Cells were harvested and radioactivity was measured as previously described (Barile and Cardona 1998; Barnes et al ., 1990). …”
Section: Methodsmentioning
confidence: 99%
“…Pharmaceutical safety was evaluated by in vitro and in vivo testing. Many studies have shown the strong correlation between in vitro cytotoxicity and in vivo animal experiments (Barile and Cardona ; Dierickx ). In the in vitro experiments, we aimed to assess whether 2‐AI/T in the concentration range that effectively inhibited bacteria biofilm can affect the oral tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxicity testing is a screening tool that typically uses cell lines for ranking acute toxicities of compounds based on alterations in cellular functions that are common to all mammalian cells (Barile & Cardona, 1998). Several cell lines including metabolically competent cells, such as primary cultured hepatocytes, can be used to detect the biotransformation of molecules and generation of reactive or toxic metabolites (Gómez-Lechón et al, 2001).…”
Section: Research Articlementioning
confidence: 99%